Burrow use and sexual dimorphism as indicators of the mating system in the symbiotic pea crab Austinixa patagoniensis (Rathbun 1918) (Decapoda, Brachyura, Pinnotheridae) - João, Marcio C. A. [UNESP]; Hernáez, Patricio (Wiley, 2021)
Brachyuran crabs of the family Pinnotheridae De Haan are a classic example of symbiotic lifestyle. Here, we described the host-use pattern, relative growth and sexual dimorphism of Austinixa patagoniensis (Rathbun 1918), a symbiont of the ghost shrimp Callichirus major (Say 1818). We use these analyses to test the A. patagoniensis mating system considering that monogamous species inhabit their respective host as male–female pairs and have a low degree of sexual dimorphism. Austinixa patagoniensis showed a high social plasticity, with individuals inhabiting galleries in solitary, in pairs, in trios or in groups of up to eight crabs. While it is true that 38% of the burrows sampled harbored pairs of crabs, the body size of paired crabs from the opposite sex was poorly correlated. This suggests that heterosexual pairing is short term with frequent shifts among burrows by male and/or female crabs, as reported before for other symbiotic decapods in which the body size of paired crabs is poorly correlated. A considerable proportion of the ovigerous females (34%) were found living solitarily, which suggest that males abandon these females shortly after insemination. The sexual dimorphism in terms of body and cheliped size was evident in this species, a condition that argues in favor of male–male competition in A. patagoniensis. The observations above argue against the notion that A. patagoniensis is monogamous. Lastly, our results revealed that body size and chelipeds of males are not under sexual selection by females, thus reinforcing the idea that male–male competition is the mechanism behind sexual selection in A. patagoniensis.
Keywords: pea crab; promiscuity; relative growth; sexual selection; symbiotic